ASME proposals for reform of SHO training: threat or opportunity for the specialty of accident and emergency?. Issue 3 (1st May 2002) - Reid, C
Abstract : A report is made on proposals for change in postgraduate medical training that may have profound implications for the specialty of accident and emergency (A&E). The proposals are detailed with their background and rationale, together with some of their possible effects on A&E.